1990
DOI: 10.1002/cyto.990110708
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Azotobacter vinelandii with correlation of coulter cell size, flow cytometric parameters, and ultrastructure

Abstract: When Azotobacter vinelandii is grown under nitrogen-fixing conditions, the mean cell volume fluctuates from 2.7 to 6.6 pm3 as determined using a Coulter counter. When NH,Cl is supplied as nitrogen source, the mean cell volume fluctuates from 4.6 to 7.4 pm3. Parallel experiments using flow cytometric measurements show similar characteristic fluctuations in the narrow forward angle light scattering signal and also in cellular protein content as determined using fluorescein isothiocyanate (FITC) fluorescence. Flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 37 publications
2
29
0
2
Order By: Relevance
“…Relationships between forward light scatter and bacterial size have been reported, although not always involving bacterioplankton Allman et al, 1990;DeLeo and Beveye, 1996;Troussellier et al, 1999), but some authors have also reported an almost complete lack of relationship between forward and side scatter and bacterial size, either throughout the growth cycle of bacteria or in natural samples (Christensen et al, 1993;Heldal et al, 1994). Relationships between the total amount of protein in a culture and the amount of light scattered have also been established (i.e.…”
Section: Bacterial Size Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between forward light scatter and bacterial size have been reported, although not always involving bacterioplankton Allman et al, 1990;DeLeo and Beveye, 1996;Troussellier et al, 1999), but some authors have also reported an almost complete lack of relationship between forward and side scatter and bacterial size, either throughout the growth cycle of bacteria or in natural samples (Christensen et al, 1993;Heldal et al, 1994). Relationships between the total amount of protein in a culture and the amount of light scattered have also been established (i.e.…”
Section: Bacterial Size Determinationmentioning
confidence: 99%
“…Somehow surprisingly, what researchers were worried about 20 years ago was quite similar to the problems we are interested with natural bacteria today: determination of DNA (Paau et al, 1977) and protein (Hutter and Eipel, 1978), differentiation of "live" and "dead" cells (Hutter and Eipel, 1978) and separation of microorganisms on the basis of DNA content and the presence of chlorophyll (Paau et al, 1979). The first studies applying flow cytometry to bacteria dealt with the description of the macromolecular composition of bacterial cells during the growth cycle: changes in DNA were found to correlate with the fluorescence of the probes used (see below), changes in protein content with changes in bacterial size (Allman et al, 1990) and changes in the scatter of light by the cells have been found to reflect changes in bacterial size (Allman et al, 1990) or the accumulation of reserve polymers such as poly-ß-hydroxybutirate (e.g. Srienc et al, 1984).…”
Section: Bacteria and Flow Cytometrymentioning
confidence: 99%
“…Total protein content of individual bacteria was determined by measuring fluorescence after staining with FITC. This is a widely adopted procedure, validated for bacteria (Allman et al, 1990) and eukaryotes (Lloyd, 1993). Ethanol-fixed bacteria were centrifuged to remove fixative, and washed and resuspended in ice-cold Tris/HCI buffer (10 mM, pH 7-4).…”
Section: Planktonic Culturesmentioning
confidence: 99%
“…A sua movimentação é realizada por flagelos e, embora sejam aeróbias, estas bactérias podem crescer em concentrações baixas de oxigênio. 38,39 As bactérias do gênero Azotobacter são quimio-organotróficas, utilizam açúcares, álcoois e sais inorgânicos para crescerem. Em vida livre, fixam em média 10 mg de nitrogênio por grama de carboidrato (glicose) consumido e para esta atividade requerem molibdênio, que pode ser parcialmente substituído por vanádio.…”
Section: A Bactéria Azotobacter Vinelandiiunclassified
“…Este tamanho pode estar associado com o fato da A. vinelandii ser uma bactéria poliplóide. 38 Contrastando com P. aeruginosa, somente o alginato sintetizado pela A. vinelandii apresenta uma seqüência de monômeros na sua estrutura química similar ao obtido de algas, 40 sob várias condições de cultura, sendo esta bactéria considerada como fonte potencial de alginatos para fins técnicos. Diversos laboratórios industriais têm tentado elucidar a rota biossintética, as condições de crescimento e a fisiologia bacteriana que levam à produção de polissacarídeos.…”
Section: A Bactéria Azotobacter Vinelandiiunclassified